Evaluation and Retrofit of Circular Reinforced Concrete Silos Built in Lima, Peru, in the 1970s - Jorge Bazan; Victor Fernandez-Davila (Journal of Rehabilitation in Civil Engineering)
The assessment of two circular reinforced concrete (RC) silos built in the 1970s is presented. The methodology implemented includes data collection, testing, analysis requirements, structural modeling, evaluation results, and retrofit design. The RC silos were originally designed in the 1970s with very low seismic demand and insufficient engineering details. Evaluation of this specialized structure has reported both stability and strength, as well as severe issues that need to be addressed. National and international codes and guidelines were consulted to define the most appropriate seismic demand, gravitational, and incidental loads, as well as load combination criteria, evaluation and diagnostic requirements, structural design criteria, and effective retrofitting techniques. The main retrofit strategy focused on improving the stability of the silos against overturning, reducing normal stresses on the ground, and strengthening the RC walls to withstand combined axial and bending effects in line with current requirements. The retrofit design included foundation extension and RC jacketing of the silo walls to address these issues. A rational approach to evaluating and retrofitting this type of non-conventional RC structure was developed. Additionally, a cost assessment based on the comparison of concrete and steel reinforcement volumes between the existing silo and the strengthened components is presented.